2014
DOI: 10.1016/j.celrep.2014.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for JNK and IKK Activation in Agouti-Related Peptide Neurons in the Development of Obesity and Insulin Resistance

Abstract: Activation of c-Jun N-terminal kinase 1 (JNK1)- and inhibitor of nuclear factor kappa-B kinase 2 (IKK2)-dependent signaling plays a crucial role in the development of obesity-associated insulin and leptin resistance not only in peripheral tissues but also in the CNS. Here, we demonstrate that constitutive JNK activation in agouti-related peptide (AgRP)-expressing neurons of the hypothalamus is sufficient to induce weight gain and adiposity in mice as a consequence of hyperphagia. JNK activation increases spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 66 publications
6
75
0
1
Order By: Relevance
“…We speculated that the possible reasons for the different phenotypes observed in our study and those of the other work [42,50] could be as follows: XBP1 splicing represents one of the downstream pathways from the activation of the RNase domain of IRE1α, whereas other signalling pathways might also be activated or inhibited by the knockout of IRE1α, which may contribute to the lean phenotype in PIKO mice. For example, altered expression of hypothalamic c-Jun N-terminal kinases (JNK), as a downstream target of the kinase domain of IRE1α [17], also regulates obesity and its related diseases [51,52]. Interestingly, the expression of ER stress markers, including phosphorylated eukaryotic translation initiation factor 2α (p-eIF2α), BiP and activating transcription factor 4 (ATF4) [27] was decreased in the hypothalamus of PIKO mice under both standard chow diet and HFD (electronic supplementary material, figure S4), suggesting another possibility in explaining the effects of IRE1α deficiency in POMC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the possible reasons for the different phenotypes observed in our study and those of the other work [42,50] could be as follows: XBP1 splicing represents one of the downstream pathways from the activation of the RNase domain of IRE1α, whereas other signalling pathways might also be activated or inhibited by the knockout of IRE1α, which may contribute to the lean phenotype in PIKO mice. For example, altered expression of hypothalamic c-Jun N-terminal kinases (JNK), as a downstream target of the kinase domain of IRE1α [17], also regulates obesity and its related diseases [51,52]. Interestingly, the expression of ER stress markers, including phosphorylated eukaryotic translation initiation factor 2α (p-eIF2α), BiP and activating transcription factor 4 (ATF4) [27] was decreased in the hypothalamus of PIKO mice under both standard chow diet and HFD (electronic supplementary material, figure S4), suggesting another possibility in explaining the effects of IRE1α deficiency in POMC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it remained undefined whether acute activation of AgRP and POMC neurons exerts acute glucose and insulin sensitivity regulatory effects and if so, which mechanism(s) are involved in this regulation both within the CNS as well as in peripheral organs. Exactly defining the food intake and glucose regulatory functions of these neurons is of critical importance, since obesity-associated hypothalamic inflammation and associated alterations of AgRP neuron activity can contribute to the manifestation of obesity and progression of insulin resistance (Tsaousidou et al, 2014; Kleinridders et al, 2009; Belgardt et al, 2010). Moreover, improved glucose metabolism in high fat diet (HFD)-fed mice upon toxin-mediated ablation of AgRP-neurons further highlights the dependence of metabolic alterations in obesity on the activity of these cells (Joly-Amado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting the hypothalamic ERK1/2 and p38 pathways prevent NPY synthesis and secretion (Kim et al, 2010). Additionally, Tsaousidou et al (2014) demonstrated that the inhibition of JNK induces hyperphagia via the up-regulation of AGRP gene expression.…”
Section: Introductionmentioning
confidence: 99%